2007
DOI: 10.1002/lapl.200710015
|View full text |Cite
|
Sign up to set email alerts
|

Cr:ZnSe prism for broadly tunable mid-infrared laser radiation generation

Abstract: Compact broadly tunable Cr:ZnSe laser was constructed and described. Cr:ZnSe bulk crystal was grown by the Bridgman technique. In our best knowledge the bulk Cr:ZnSe prism was utilized as laser active media and simultaneously as an intra-cavity dispersive element for the first time. The maximal output pulse energy was 20 mJ. The generated radiation was tunable from 2000 up to 2750 nm. The repetition-rate was 1 Hz. The generated radiation beam spatial structure was close to TEM00.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 5 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…The slope-efficiency with respect to the absorbed energy was 15%. The width of the oscillation spectrum was ∼ 100 nm and its maximum was shifted towards the longer wavelength with respect to the previously published [11][12][13] Cr.ZnSe laser about 80 nm (Fig. 6).…”
Section: Er:yag Pump Sourcementioning
confidence: 85%
“…The slope-efficiency with respect to the absorbed energy was 15%. The width of the oscillation spectrum was ∼ 100 nm and its maximum was shifted towards the longer wavelength with respect to the previously published [11][12][13] Cr.ZnSe laser about 80 nm (Fig. 6).…”
Section: Er:yag Pump Sourcementioning
confidence: 85%
“…It was found that good candidates for this mid-infrared region generation are chalcogenide materials (ZnSe, ZnS, CdSe, CdS) doped by divalent transition-metal (TM) ions as Cr 2+ , Fe 2+ , Co 2+ , etc. [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the wavelength range around 2.5 lm, the chromium doped materials as ZnSe:Cr 2+ , ZnS:Cr 2+ [1][2][3][4]8,9], CdSe:Cr 2+ [10,11], CdS:Cr 2+ [12,13], CdTe:Cr 2+ [14,15] were studied and the continuous-wave as well as pulsed laser regime, efficient wavelength tunability, and moreover mode-locked regime [16,17] was successfully demonstrated. As the spectroscopic properties of TM 2+ ions are significantly influenced by their local environment in the matrix, the additional possibility to modify their properties is using the solid solutions approach.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications could be found in eye-safe surgery, rapid and efficient detection of toxicants in waters, free-space communication or military usage like seeking for munitions or cruise missiles, et al Among various dopant-host combinations, Cr 2+ doped ZnS and ZnSe are the most promising ones for being employed in practical applications in short term. State-of-the-art laser demonstrations of all regimes of operation for those two systems have shown great progress in recent years, including CW (>10W) 2-3 , freerunning (>20mJ) 4 , mode-locked (70fs, 1W) 5 . The most important factor that affecting the further development of laser performance is the optical quality of the gain media.…”
Section: Introductionmentioning
confidence: 99%